2020
DOI: 10.1002/cctc.202001316
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl Methyltransferases: Natural Functions and Potential Applications in Industrial Biotechnology

Abstract: The use of methyltransferases (MTs) in industrial biotechnology to replace toxic alkylating agents is of increasing interest. Carboxyl MTs (CMTs) are a subgroup of MTs that methylate the hydroxyl oxygen of carboxylic acids. Research initially focussed on their natural functions in protein regulation and production of volatile methyl esters in plants. In this review we highlight this potentially valuable group of enzymes that show promise for formation of a wide range of structurally diverse methyl esters from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…39 Additionally, carboxyl methyltransferases such as BueF are of biotechnological interest. 40 Heterologous expression of bue genes in the chassis A. nidulans proved a more favourable strategy for the production and isolation of 1 than in the native host, obtaining a ~45-fold increase in the yield of 1 per kg of substrate compared to A. burnettii. 3 Interestingly, we also observed that the strains of A. nidulans harbouring AMA1-based episomal vectors, which require auxotrophy selection for maintenance, can sustain production in grain substrates such as jasmine rice with yields as high as 468 mg/kg in the case of 2.…”
Section: Discussionmentioning
confidence: 99%
“…39 Additionally, carboxyl methyltransferases such as BueF are of biotechnological interest. 40 Heterologous expression of bue genes in the chassis A. nidulans proved a more favourable strategy for the production and isolation of 1 than in the native host, obtaining a ~45-fold increase in the yield of 1 per kg of substrate compared to A. burnettii. 3 Interestingly, we also observed that the strains of A. nidulans harbouring AMA1-based episomal vectors, which require auxotrophy selection for maintenance, can sustain production in grain substrates such as jasmine rice with yields as high as 468 mg/kg in the case of 2.…”
Section: Discussionmentioning
confidence: 99%
“…37 Additionally, carboxyl methyltransferases such as BueF are of biotechnological interest. 38 Heterologous expression of bue genes in the chassis A. nidulans proved a more favourable strategy for the production and isolation of 1 than in the native host, obtaining a ~45-fold increase in the yield of 1 per kg of substrate compared to A. burnettii. 4 Interestingly, we also observed that the strains of A. nidulans harbouring AMA1-based episomal vectors, which require auxotrophy selection for maintenance, can sustain production in grain substrates such as jasmine rice with yields as high as 468 mg/kg in the case of 2.…”
Section: Discussionmentioning
confidence: 99%
“…37 Additionally, carboxyl methyltransferases such as BueF are of biotechnological interest. 38 Heterologous expression of bue genes in the chassis A. nidulans proved a more favourable strategy for the production and isolation of 1 than in the native host, obtaining a ~45-fold increase in the yield of 1 per kg of substrate compared to A. burnettii. 4 Interestingly, we also observed that the strains of A. nidulans harbouring AMA1-based episomal vectors, which require auxotrophy selection for maintenance, can sustain production in grain substrates such as jasmine rice with yields as high as 468 mg/kg in the case of 2.…”
Section: Discussionmentioning
confidence: 99%